TECHNICAL EFFICIENCY OF SAVING AND LOAN COOPERATIVES IN GERBANGKERTASUSILA, EAST JAVA PROVINCE: A TWO-STAGE ANALYSIS - Mochamad Fajar Insani; Atik Purmiyati (East Java Economic Journal, 2019)
The purpose of this research is to assess the level of technical efficiency of the Savings and Loans Cooperative (KSP) in Gresik, Bangkalan, Mojokerto, Surabaya, Sidoarjo, and Lamongan (Gerbangkertasusila), Indonesia, and to identify the factors that influence the level of technical efficiency of the Savings and Loans Cooperative in Gerbangkertasusila. Two Stage Analysis that used are Data Envelopment Analysis and Tobit regression. Variables are used in the DEA as output, specifically the remainder of the cooperative’s business (SHU), whereas input includes the number of members, own capital, number of employees, and business volume. The second stage involves analyzing the determinants of technical efficiency using Tobit regression, with the independent variables being cooperative age, external capital, assets, and managers. The results showed that the average level of technical efficiency of the KSP was 60.4 percent, with 16 KSP being the most efficient. Meanwhile, the Tobit regression results show that simultaneously the variables have an influence on the level of technical efficiency of the KSP. Partially the cooperative age and external capital variables have no significant effect on savings and loan cooperatives, while asset and managers have a significant positive effect on the level of technical efficiency of savings and loan cooperatives.